Modificações nos teores de carboidratos em tubérculos de batata (Solanum tuberosum L) armazenados a diferentes temperaturas - Furtado , Márcio Henrique; Fernandes Lopes , Nei; Oliva, Marco Antonio; Mizubuti , Aquira (Revista Ceres, 2025)
Seed-tubers of Solanum tuberosum L. of the cultivars Mantiqueira and Bintje were stored in dark chambers at 5o, 10°, 20o + 1°C and at room temperature (18o to 27°C) for 154 days. Starch, total soluble sugars, and reducing sugar levels were determined at 14-day intervals during this storage period.